2003
DOI: 10.1046/j.1468-2982.2003.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Eletriptan for the Treatment of Migraine in Patients with Previous Poor Response or Tolerance to Oral Sumatriptan

Abstract: To determine the tolerability and efficacy of eletriptan in patients who had discontinued oral sumatriptan due to lack of efficacy or intolerable adverse events (AEs) during previous clinical treatment (not a controlled trial). Eletriptan is a potent, selective 5-HT1B/1D receptor agonist with beneficial pharmacokinetic properties compared with sumatriptan. In a double-blind, parallel group, placebo-controlled multicentre study, patients with and without aura (n = 446) were randomized to 40 mg eletriptan (E40, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(92 citation statements)
references
References 19 publications
5
87
0
Order By: Relevance
“…Eletriptan has demonstrated within-patient consistency of response based on three previous studies using a randomized, double-blind, placebo-controlled, parallelgroup design (10)(11)(12). For eletriptan 40 mg (ELE-40), consistency of response on two out of three attacks ranged from 63% to 77%, and for eletriptan 80 mg (ELE-80), two out of three consistency ranged from 72% to 82%.…”
Section: Introductionmentioning
confidence: 99%
“…Eletriptan has demonstrated within-patient consistency of response based on three previous studies using a randomized, double-blind, placebo-controlled, parallelgroup design (10)(11)(12). For eletriptan 40 mg (ELE-40), consistency of response on two out of three attacks ranged from 63% to 77%, and for eletriptan 80 mg (ELE-80), two out of three consistency ranged from 72% to 82%.…”
Section: Introductionmentioning
confidence: 99%
“…The response rates achieved here with almotriptan cannot be compared directly with those achieved in the trials discussed above [10,12,13] . Although all of the trials recruited patients with a history of poor response to sumatriptan, their study designs were different.…”
Section: Discussionmentioning
confidence: 85%
“…Three other studies have investigated the effi cacy of switching triptan therapy in patients who were poor responders to sumatriptan [10,12,13] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both sumatriptan and eletriptan were well tolerated, with low incidence of adverse effects [Goadsby et al 2000;Mathew et al 2003b;Sandrini et al 2002]. Moreover, eletriptan (compared with placebo) has been demonstrated as effective in treating acute migraine in previous nonresponders, or patients not tolerant to sumatriptan [Färkkilä et al 2003]. Other triptan-switch studies reported eletriptan 40 mg efficacy in migraineurs who did not also respond to treatment with rizatriptan and NSAIDs [Bhambri et al 2015].…”
Section: Eletriptan: Efficacy In Head-to-head Studiesmentioning
confidence: 99%